P173 Patency capsule: A novel independent predictor for long-term outcomes among patients with quiescent Crohn's disease. (30th January 2023) - Ukashi, O; Kopylov, U; Ungar, B; Haj-Natour, O; Selinger, L; Neuman, S; Yanai, H; Dotan, I; Yablecovitch, D; Lahat, A; Eliakim, R; Ben-Horin, S
Abstract: Background: Patency capsule (PC) is a recommended procedure to rule-out small-bowel stenosis before video capsule endoscopy (VCE).We examined future clinical outcomes among patients with failed-PC versus patients in whom PC had passed (passed-PC). Methods: A Post-hoc analysis of two prospective cohort studies of adult patients with quiescent small-bowel CD that underwent PC between 2013-2020. The primary composite-outcome was the need for intestinal-surgery or endoscopic-dilation during follow-up in patients with or without failed-PC. Results: A total of 191 patients were included (47-failed PC, 144-passed PC, median follow-up 34.12 months). Patients with a failed-PC had higher rates of the primary composite-outcome (21.3% vs. 1.4%, Hazard ratio [HR] 20.4, 95% confidence interval [CI] 4.4-94.1, p<0.001) and also secondary outcomes including intestinal-surgery (14.9% vs. 0.70%, p<0.001), endoscopic-dilation (14.9% vs. 0.70%, p<0.001), admissions (23.3% vs. 5.7%, p<0.001) and clinical-flares (43.9% vs. 27.5%, p=0.005) during follow-up compared with controls. Failed-PC was the only statistically significant factor for surgery and/or endoscopic-dilation, regardless of a B2/B3 phenotype at baseline. In sensitivity-analyses restricted only to patients with stricturing phenotype (n=74), failed-PC still predicted worse long-term composite-outcome (HR 23.1 95% CI 2.3-228.0, p=0.007). Of the 191 patients ingesting a PC, only one patient with a failed-PC had 48 hours of self-limiting mild symptoms Conclusion: Clinically-stable CD patients with failed-PC have worse long-term clinical outcomes than those without, independently of CD phenotype. Standalone PC may serve as a novel, safe and affordable prognostic examination to stratify patients with CD for future risk of poor outcomes and potentially guide pre-emptive management decisions.